Kedudukan Camat Selaku Pejabat Pembuat Akta Tanah Sementara - Hamzah Hamzah (Puslatbang KHAN, 2019)
“Camat” is the subdistrict leader, “Camat” or other designation is also a leader and coordinator of government administration in the subdistrict working area, and “Camat” can be appointed as an Acting Officer for the Temporary Land Deed for working areas where the official Deed Formation Officer is not sufficient. The formulation of the problem is how the position of a sub-district head as an official land deed maker. The purpose of this research is to find out about the position of the sub-district head as an official land deed maker. The approach used in this research is a statute approach, which is normative in nature, meaning that the study or discussion is emphasized on aspects of formal legal rules in force. The results of the research show that the position of the sub-district head as an official of the temporary land deed maker remains legal and valid.